Back to the Future: Re-Engineering the Evolutionarily Lost Arbuscular Mycorrhiza Host Trait to Improve Climate Resilience for Agriculture - Hornstein, Eli D.; Sederoff, Heike (Critical reviews in plant sciences, 2024)
The coming century in agriculture will be marked by increasing exposure of crops to abiotic stress and disease due to climate change. The plant traits with the strongest potential to mitigate these stresses are complex, and are increasingly recognized to involve interaction with the microbiome. Through symbiosis with soil fungi, plants form arbuscular mycorrhizae (AM) that can alleviate nutrient, water, and temperature stress, and can confer pathogen resistance and increased yield. The portfolio of advantages offered by AM overlaps with the benefits of agriculturally useful plant traits that have been the subject of decades of intensive biotechnological efforts, such as C4 photosynthesis and rhizobial nitrogen fixation. In this article we illustrate the prospective benefits of genetic engineering to produce AM in nonmycorrhizal plants and modify AM in already-mycorrhizal crops. We highlight recent advances which have clarified the key genetic and metabolic components of AM symbiosis, and show that many of these components are involved in other plant biological processes and have already been subject to extensive genetic engineering in nonsymbiotic contexts. We provide a theoretical research roadmap to accomplish engineering of AM into the nonmycorrhizal model Arabidopsis including specific molecular genetic approaches. We conclude that AM is potentially more tractable than other complex plant traits, and that a concerted research initiative for biotechnological manipulation of AM could fill unique needs for agricultural resilience. Finally, we note that engineering of AM provides a potential back door into manipulation of other essential plant traits, including carbon storage, and beneficial microbiome assembly.